2022
DOI: 10.1186/s40793-021-00396-9
|View full text |Cite
|
Sign up to set email alerts
|

Land-use intensification differentially affects bacterial, fungal and protist communities and decreases microbiome network complexity

Abstract: Background Soil microbial communities are major drivers of cycling of soil nutrients that sustain plant growth and productivity. Yet, a holistic understanding of the impact of land-use intensification on the soil microbiome is still poorly understood. Here, we used a field experiment to investigate the long-term consequences of changes in land-use intensity based on cropping frequency (continuous cropping, alternating cropping with a temporary grassland, perennial grassland) on bacterial, proti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 93 publications
4
24
0
1
Order By: Relevance
“…Organic fertilizer amendment increased the relative abundance of bacterivorous and omnivorous protists but reduced plant pathogenic protists (Xiong et al, 2018). Additionally, recent study in a long-term field experiment under different levels of land-use intensity has shown that land management not only had a major impact on the structure and composition of bacterial, protistan and fungal communities but also affected microbiome network complexity (Romdhane et al, 2022). In a recent study, Bazany et al (2022) found that water deficit stress can significantly influence inter-kingdom microbial connections in the rhizospheres of corn and sugar beet.…”
Section: Microbial Interactions and Keystone Taxa Of Crop-associated ...mentioning
confidence: 99%
“…Organic fertilizer amendment increased the relative abundance of bacterivorous and omnivorous protists but reduced plant pathogenic protists (Xiong et al, 2018). Additionally, recent study in a long-term field experiment under different levels of land-use intensity has shown that land management not only had a major impact on the structure and composition of bacterial, protistan and fungal communities but also affected microbiome network complexity (Romdhane et al, 2022). In a recent study, Bazany et al (2022) found that water deficit stress can significantly influence inter-kingdom microbial connections in the rhizospheres of corn and sugar beet.…”
Section: Microbial Interactions and Keystone Taxa Of Crop-associated ...mentioning
confidence: 99%
“…Co-occurrence analysis was used to inspect the association between core apicomplexan and metazoan taxa. Although co-occurrence analysis might not reflect the true complexity of host-parasite interactions, this integrative approach can help to better understand how taxonomic identity and land-use change affect the associations between host and parasite taxa 41 . Specifically, we calculated Spearman's correlations between the abundance of the top 20% abundant apicomplexan OTUs and the top 20% abundant OTUs of Arthropoda, Nematoda and Annelida.…”
Section: Statisticsmentioning
confidence: 99%
“…Manipulating the soil microbiota is an effective way to alleviate GRP ( Lee et al., 2015 ; Dong et al., 2018 ; Seo et al., 2019 ). Several agricultural practices can shape the soil microbial structure ( Romdhane et al., 2022 ), which can result in either positive ( Qi et al., 2020 ) or negative outcomes on plant health ( Bziuk et al., 2021 ). For example, continuous cropping of ginseng affects the taxonomic and functional diversity of the soil microbial population and the potential pathogenic genera, increasing the risk of soil conduciveness ( Zhang et al., 2020 ; Tong et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%